Pengelolaan Wisata Edukasi Berbasis Lingkungan sebagai Media Pembelajaran Alam di Kebun Raya Bogor - Nadia Anastasya Nathania; Roels Ni Made Sri Puspadewi (Fakultas Teknik Universitas Cenderawasih, 2026)
The Bogor Botanical Gardens serves as a prominent nature-based educational tourism destination that utilizes its rich, living environment as a primary learning medium. This research aims to comprehensively understand and analyze the specific strategies employed by the management of Bogor Botanical Gardens in operating its environmental-based educational tourism. While the Bogor Botanical Gardens possesses immense potential to serve as a world-class center for ex-situ conservation and environmental education, its educational function has not yet been fully optimized to reach its maximum impact. Consequently, this study seeks to identify existing operational gaps and uncover strategic opportunities for improvement. To achieve a profound understanding of the complex dynamics in the field, this study adopts a qualitative approach utilizing an educational research design. This framework allows for a nuanced exploration of how educational programs are delivered and received. Data collection was meticulously carried out through a combination of: Field observations of ongoing tour programs and visitor interactions, Semi-structured interviews designed to capture diverse, first-hand perspectives, and Documentation review of internal management guidelines and educational materials.